Practical Tips and Techniques for Injection Rhinoplasty - Singh, Sukhbir (J Cutan Aesthet Surg, 2019)
BACKGROUND: Nose is an important part of facial aesthetics and needs to be restored as part of overall facial rejuvenation. Nasal fillers containing hyaluronic acid give immediate results with minimal or no downtime. MATERIALS AND METHODS: The aim of this article was to give an insight and practical tips to enhance results with nasal fillers and at the same time minimize complications. All the procedures were performed at the author’s private clinic and by the author himself. RESULTS: Dorsal correction has been the most common indication for nasal fillers, followed by the tip and alar correction. The patients are highly satisfied if proper care is taken during injections, which leads to gratifying results. CONCLUSION: Hyaluronic fillers are very effective for nasal reshaping for patients not willing for rhinoplasty and even for those with minor defects after rhinoplasty. They give immediate results with very minimal downtime.